2017
DOI: 10.1039/c7cc00358g
|View full text |Cite
|
Sign up to set email alerts
|

A gold nanoparticle-mediated rapid in vitro assay of anti-aggregation reagents for amyloid β and its validation

Abstract: Herein, we report a rapid in vitro assay of amyloid β anti-aggregation reagents using gold nanoparticles as nucleation cores and optical reporters. Based on the colorimetric responses observed with the naked eye, effective anti-aggregation reagents were rapidly (<15 min) distinguished. For these reagents, conventional methods showed fewer amyloid β aggregates and an increased viability of neuroblastoma cells after treatment. We envision that our proposed method will facilitate the discovery of efficient drug c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…Aβ-GNP aggregation, 26 previous studies have suggested that the electrostatic interaction between Aβ and GNPs plays a significant role in Aβ-GNP aggregation through rapid aggregate formation under acidic pH conditions (pH 2− 3). 21,25 However, our observation suggested that acidic pH can disrupt colloidal states of GNPs and produce the SPR red shifting that is identical to the one generated by Aβ-GNP aggregation. Previous studies also showed that colloidal dispersion of GNPs is influenced by pH and ionic strength.…”
Section: Although Various Intermolecular Interactions Can Influencementioning
confidence: 71%
See 3 more Smart Citations
“…Aβ-GNP aggregation, 26 previous studies have suggested that the electrostatic interaction between Aβ and GNPs plays a significant role in Aβ-GNP aggregation through rapid aggregate formation under acidic pH conditions (pH 2− 3). 21,25 However, our observation suggested that acidic pH can disrupt colloidal states of GNPs and produce the SPR red shifting that is identical to the one generated by Aβ-GNP aggregation. Previous studies also showed that colloidal dispersion of GNPs is influenced by pH and ionic strength.…”
Section: Although Various Intermolecular Interactions Can Influencementioning
confidence: 71%
“…For Aβ aggregation, the 9:1 ratio of Aβ 40 and Aβ 42 was used as suggested in a previous study . Briefly, 10 μM Aβ 40 and 10 μM Aβ 42 solution was prepared fresh in 1× PBS from the stock solution (1 mg/mL) before use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…et al(Kim et al 2017) suggested that AuNPs could act as an effective gene regulator and decrease the aggregation of Aβ. In addition, AuNPs have a protective effect on Aβ1-42-induced apoptosis, and the process is related to NF-KB-induced neuroin ammation(Ali et al 2016).…”
mentioning
confidence: 99%